Choking under Pressure: Evidence of the Causal Effect of Audience Size on Performance - René Böheim; Dominik Grübl; Mario Lackner (Institute of Labor Economics (IZA), 2018)
We analyze performance under pressure and estimate the causal effect of audience size on the success of free throws in top-level professional basketball. We use data from the National Basketball Association (NBA) for the seasons 2007/08 through 2015/16. We exploit the exogenous variation in weather conditions on game day to establish a causal link between attendance size and performance. Our results confirm a sizeable and strong negative effect of the number of spectators on performance. Home teams in (non-critical) situations at the beginning of games perform worse when the audience is larger. This result is consistent with the theory of a home choke rather than a home field advantage. Our results have potentially large implications for general questions of workplace design and help to further understand how the social environment affects performance. We demonstrate that the amount of support, i.e. positive feedback, from a friendly audience does affect performance.
Keywords: D03; J24; M54; 330; performance under pressure; choking; paradoxical performance effects on incentives; social pressure